Discrete-Variable Extremum Problems - Dantzig, George B. (Operations Research, 1957)
This paper reviews some recent successes in the use of linear programming methods for the solution of discrete-variable extremum problems. One example of the use of the multistage approach of dynamic programming for this purpose is also discussed.